1997
DOI: 10.1007/bf01978968
|View full text |Cite
|
Sign up to set email alerts
|

The study of the dehydration and dehydroxylation of smectites by emanation thermal analysis

Abstract: The dehydration and dehydroxylation of the smectites, beidellite and montmorillonite (dioctahedral) and saponite and laponite (trioctahedral), were investigated by ETA, DTA, TG and Xray diffractions. There are differences between the behaviors of di-and trioetahedral clays which are due to the differences in the ability of the exchangeable cations to migrate into hexagonal holes of the SiO 4 network and due to the fact that the dehydroxylation and reerystallization of dehydroxylated trioctahedral smectites occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 50 publications
(15 citation statements)
references
References 10 publications
1
14
0
Order By: Relevance
“…Emanation Thermal Analysis (ETA) [8,9], based on the measurement of radon release from samples previously labeled, was used to characterize microstructure changes during "in situ" heating of the samples. The ETA has been previously used in the characterization of the thermal behavior of various minerals, such as kaolinite [10], saponite, beidelite [3], vermiculite [11][12][13], boehmite [14], pyrophyllite, talc [15], brannerite [16], haematite [17].…”
Section: +mentioning
confidence: 99%
See 2 more Smart Citations
“…Emanation Thermal Analysis (ETA) [8,9], based on the measurement of radon release from samples previously labeled, was used to characterize microstructure changes during "in situ" heating of the samples. The ETA has been previously used in the characterization of the thermal behavior of various minerals, such as kaolinite [10], saponite, beidelite [3], vermiculite [11][12][13], boehmite [14], pyrophyllite, talc [15], brannerite [16], haematite [17].…”
Section: +mentioning
confidence: 99%
“…In order to understand the environmental behaviour of monmorillonite clay minerals their dehydration and dehydroxylation on heating has been studied by several authors [1][2][3][4][5][6][7]. It was found that differences in the montmorillonite dehydration are due to a more or less strong ) the ion is more important that the interlayer surface, but for larger divalent cations as well as for monovalent cations the influence of the layered surface on the hydration is dominant.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Dehydroxylation endothermic peaks for these particular clays are 650 and 810~ respectively [21]. Each of the clays showed variable basal spacings ( Fig.…”
Section: Slides Heated At 600~mentioning
confidence: 98%
“…(For this particular clay the endothermic peak was determined to be 530~ [21 ] and this would allow a condensation reaction to take place such that an A1-O-clay bond formed [ …”
Section: Slides Heated At 500~mentioning
confidence: 99%